Determinan Kelemahan Sistem Pengendalian Intern pada Laporan Keuangan Pemerintah Kabupaten dan Kota Se-Kalimantan Barat - Bob Mustafa; Mahyus Mahyus (Eksos, 2017)
This study aims to investigate the influence of variables of regional complexity, capital expenditure, local revenue, and economic growth on the weakness of internal control of district and city government financial reporting for West Kalimantan for the period 2010-2014. The study used a saturated sample consisting of 14 district and city governments in West Kalimantan. Significant test of multiple linear regression analysis of panel data is done through software Eviews 9. The results show that partially complexity of area and PAD have significant influence to SPI weakness variable, while capital expenditure and economic growth partially have no significant influence to SPI weakness. The result of F test shows that together variables of regional complexity, capital expenditure, PAD, and economic growth have significant influence to SPI weakness.